Pendidikan Islam Multikultural di Pesantren ( Studi Kasus Pada Pondok Pesantren Sirojul Ulum Semanding Pare Kediri ) - Muchasan, Ali (Ali Muchasan, 2018)
Islamic boarding school Sirojul Ulum as one of the Islamic educational institutions established to create peace and provide a wider insight into the horizon of thought, scholarship and experience for Muslims. This institution is a manifestation and implementation of the aspirations and hopes of Kediri Muslims to create an educational institution that is able to print leader of the people, especially the Kediri Muslims qualified. The method used in this research is descriptive method. The study design was a descriptive qualitative. The data were analyzed, using data reduction, data presentation, and data verification either inductive, deductive and comparative. The results showed that the Modern Islamic Boarding School Sirojul Ulum Pare has instilled multicultural education to the students. This is illustrated by the religious values are imparted to the students such as brotherhood (fraternity), cooperation, struggle that are all taught equality of human rights.